O Rio de Janeiro no cenário discursivo: a cidade-texto de João do Rio - Mariana Pereira Dias (2016)
The turning of the 19th to the 20th century and the first years of this century were significant for the arrival and establishiment of modernity in Brazil, both in the political sense, with the proclamation of the Republic and its establishment, as in social habits. The biggest scenario of these changes was Rio de Janeiro, the federal capital of the country, which underwent in a significant reform to adapt to modernity in the city structure and citizens education, still attached to traditional values.This paper studies the work A alma encantadora das ruas (1908) by João do Rio, a journalist who was at the most important events that characterized the inclusion of Rio in the modern scenario. The objective of this study is to determine on what extent João do Rio, through the chronicles of this work - with all its peculiarity of "minorgenre", as stated by Antonio Candido (1992, p. 13) that develops within the journalism - can do a reading of the city of Rio de Janeiro in this century turning, noting modernity critically in its core and deconstructing the concepts crystallized by the current bourgeoisie.For this, the work was divided into two parts: the first seeks to trace a historical overview, contextualizing the urban reform and discussing different views on it from chroniclers of the time as Olavo Bilac, Lima Barreto and the own João do Rio for from then on, to understand the place of the man of letters in this new scenario and understand how chronic became part so actively in the literature of the time. From this point, we show how João do Rio merges the reporter to modern artist, the flâneur, which moves through the streets trying to read the city unreadable in its gigantism. The second and final part of the paper researches each chronicle of the book A alma encantadora das ruas (1908), organizing them and emphasizing aspects of its structure and aesthetic resources used by João do Rio as the embodiment of the street, in order to take a reading of Rio de Janeiro through the emblem of the dividedcity: on one side, exhibiting its modernized facet, on another hiding the poverty of the large part of the population, who had to find a way to survive.